2000
DOI: 10.1074/jbc.m006854200
|View full text |Cite
|
Sign up to set email alerts
|

New Structural and Functional Aspects of the Type I Interferon-Receptor Interaction Revealed by Comprehensive Mutational Analysis of the Binding Interface

Abstract: Type I interferons bind to two cell surface receptors, ifnar1 and ifnar2, as the first step in the activation of several signal transduction pathways that elicit an antiviral state and an anti-proliferative response. Here, we quantitatively mapped the complete binding region of ifnar2 on interferon (IFN)␣2 by 35 individual mutations to alanine and isosteric residues. Of the six "hot-spot" residues identified (Leu-30, Arg-33, Arg-144, Ala-145, Met-148, and Arg-149), four are located on the E-helix, which is loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
164
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(171 citation statements)
references
References 37 publications
7
164
0
Order By: Relevance
“…The respective binding sites of IFN-␣2 and ifnar2 were previously mapped by means of site-directed mutagenesis (7,10). Here, we extended these studies by carrying out a systematic DMC analysis of the interface.…”
Section: Dmc Analysis Of the Ifn-␣2-ifnar2mentioning
confidence: 91%
See 2 more Smart Citations
“…The respective binding sites of IFN-␣2 and ifnar2 were previously mapped by means of site-directed mutagenesis (7,10). Here, we extended these studies by carrying out a systematic DMC analysis of the interface.…”
Section: Dmc Analysis Of the Ifn-␣2-ifnar2mentioning
confidence: 91%
“…IFN-␣2 and ifnar2-extracellular domain (EC) were expressed in Escherichia coli and purified, and their concentrations were determined as described (7,24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in K D values between IFN-α2c and CM3 were observed for IFNAR2-EC mutants I105A and M48V (data not shown). The importance of those amino acids for interaction with helices A (45-50) and E (102-106), as well as loop AB(78-82) of IFN-α2 has also previously been shown by Piehler et al ( , 2000. We used native electrophoresis to study differences in binding between CM3 with and without 6-histidine-tag and IFN-α2c with or without 6-histidine-tag and the IFNAR2-EC mutants I47A, I105A and M48V.…”
Section: Ifnar2-ec Mutantsmentioning
confidence: 90%
“…Interestingly enough, these differences had not been observed in the same experiments with IFN-α21b (data not show). Since it was confirmed that helix C is not involved in interaction with IFNAR2-EC (19,23), these results suggested that mutation in helix C (CM3) could affect IFN-IFNAR2-EC indirectly. The presence or absence of Nterminal 6-histidine tag had no effect on behavior of CM3.…”
Section: Ifnar2-ec Mutantsmentioning
confidence: 92%